2011
DOI: 10.1177/070674371105600308
|View full text |Cite
|
Sign up to set email alerts
|

Concept de soi physique et adolescents présentant une déficience intellectuelle: Effets de l'âge, du sexe et de la catégorie de poids

Abstract: Objectif : Etudier les effets de l'âge, du sexe, du poids et de leurs interactions sur l'estime globale de soi (EGS) et le concept de soi physique d'adolescents présentant une déficience intellectuelle (DI). Méthode : Un échantillon de 353 adolescents DI, âgés de 12 à 18 ans, a participé à cette étude. La version très courte de l'inventaire du soi physique pour adolescents DI (communément appelée PSI-VSF-ID) a été utilisée pour évaluer l'EGS et les perceptions du soi physique (la valeur physique perçue [VPP], … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 41 publications
(80 reference statements)
1
3
0
1
Order By: Relevance
“…These fluctuations in self-esteem in adolescence observed in this study are also related to the male and female gender since low self-esteem is more marked for girls than for boys and the existence of a significant difference between the self-esteem scale score for both sexes is highlighted. This finding confirms the results of several previous studies (Seidah et al, 2004;Bégarie et al, 2011;Bolognini et al, 1996;Fourchard & Courtinat, 2013), where the authors have already observed that boys get scores overall self-esteem better than girls.…”
Section: Overall Self-esteem In Adolescentssupporting
confidence: 92%
“…These fluctuations in self-esteem in adolescence observed in this study are also related to the male and female gender since low self-esteem is more marked for girls than for boys and the existence of a significant difference between the self-esteem scale score for both sexes is highlighted. This finding confirms the results of several previous studies (Seidah et al, 2004;Bégarie et al, 2011;Bolognini et al, 1996;Fourchard & Courtinat, 2013), where the authors have already observed that boys get scores overall self-esteem better than girls.…”
Section: Overall Self-esteem In Adolescentssupporting
confidence: 92%
“…Physical fitness during childhood or adolescence is a predictor of good health in adulthood (Ortega et al, 2011). Cardiorespiratory endurance and muscle strength are among the components of physical fitness most often recommended to establish a prognosis for chronic disease risk (Bégarie et al, 2011). The objective of this study was to evaluate the physical condition of sedentary children and adolescents with intellectual disabilities, schooled in the city of Kinshasa province in comparison with children without ID.…”
Section: Discussionmentioning
confidence: 99%
“…Ces résultats s'explique par la théorie du « Big fish little pond effect » développée par Marsh [25] où « un élève scolarisé avec des individus autant, voire plus compétents que lui, aura une plus mauvaise représentation de ses performances scolaires (petit poisson dans grand bassin) par rapport à un élève scolarisé avec des individus moins compétents (grand poisson dans petit bassin) » [26] Le seconde Ancova montre un effet principal de l'âge des élèves sur la dimension « Valeur propre » pour laquelle les élèves les plus âgés ont un niveau d'estime de soi plus élevé que les élèves les plus jeunes. Ce résultat relatif à la dimension « Valeur propre » corrobore ceux obtenus dans la littérature s'intéressant aux caractéristiques développementales de l'estime de soi d'élèves en « situation de handicap » ou non [5,28,29]. Aussi, les attentes pédagogiques que les enseignants se fixent en fonction des besoins et des capacités des élèves à l'instant t et non en fonction de leur âge académique expliquent l'effet observé sur cette dimension.…”
Section: Discussion Et Conclusionunclassified